Failure In metal honeycombs manufactured by selective laser melting of 304 L stainless steel under compression - Sudharshan Anandan; Rafid M. Hussein; Myranda Spratt; Joseph Newkirk; K. Chandrashekhara; Heath Misak; Michael Walker (Virtual and Physical Prototyping, 2019)
Cellular structures, specifically honeycombs, are commonly used as core materials in sandwich structures. This is especially true in aerospace applications where high bending and out-of-plane compressive stiffness coupled with low component weight is required. Additive manufacturing techniques are well suited for the manufacture of such cellular structures in a cost-effective manner. The current work focuses on honeycombs using selective laser melting of 304 L stainless steel. The mechanical behaviour of honeycombs was evaluated using out-of-plane compression tests. A numerical model was built to describe failure of the additively manufactured honeycombs. Compression tests were performed, on cylindrical samples to build the nonlinear material model. The material behaviour was found to be dependent on the build direction. Results of experiments and simulation show that failure occurs through a plastic buckling mechanism.